Discussion on operation: To compare the curative effect of PMT and CDT in the treatment of middle and high risk stratified APE and the clinical application value of serum BNP, TnI and plasma DFR levelse - Guan, Qinglong; Liu, Chenglong; Li, Wei; Wang, Xiaofei; Gu, Ruiyuan; Wang, Ruihua; Li, Gang; Liu, Shuai (Frontiers in Surgery, 2023)
Objective:To compare the efficacy of PMT and CDT in the treatment of patients with moderate and high-risk ape and explore the clinical application value of biomarkers in the treatment of moderate and high-risk ape,Method:A total of 84 patients with ape were selected from the Department of vascular surgery of the Second Affiliated Hospital of Shandong First Medical University and the Department of vascular surgery of the Ninth People's Hospital of Shanghai Jiaotong University.According to the relevant guidelines, they were divided into high-risk group and medium risk group, including PMT group (35 cases) and CDT group (49 cases).To detect the changes of serum BNP, TnI and plasma DFR levels in different risk stratification before and after PMT and CDT, the correlation and diagnostic value of each index, and compare the thrombus clearance rate, pulmonary artery pressure, average dosage of urokinase, effective thrombolytic time, average hospitalization time and complications of PMT and CDT.Result:Under different treatment methods and risk stratification, there was no statistically significant difference in the clinical data of patients at general baseline;The preoperative BNP, TnI and DFR levels of PMT and CDT in the middle and high risk stratification were significantly lower than those in the other groups (P＜0.005),Compared with the CDT group, PMT has significantly better therapeutic effect on ape than the CDT group in terms of thrombus clearance rate, pulmonary artery pressure, average dosage of urokinase, effective thrombolytic time and average hospitalization time (P＜ 0.05),meanwhile,there was no significant difference in postoperative complications between the two groups (P＜ 0.05).After half a year of follow-up, the levels of BNP, TnI and DFR in the cured group were significantly lower than those in the effective group and the ineffective group.The areas under the curve of serum BNP, TnI and plasma DFR were 0.91, 0.87 and 0.93 and the area under the curve DFR has higher diagnostic efficiency than BNP and TnI, while the sensitivity and specificity of TnI are significantly higher than BNP and DFR.Conclusion:Serum BNP, TnI and plasma DFR levels can reflect the risk stratification and better clinical diagnostic value of ape,PMT and CDT are used to treat high-risk ape